2022
DOI: 10.1093/infdis/jiac417
|View full text |Cite
|
Sign up to set email alerts
|

The Inappropriateness of Using Rifampicin E-Test to Predict Rifabutin Resistance in Helicobacter pylori

Abstract: Background The aim of this study was to evaluate the rifamycin cross-resistance in Helicobacter pylori, and whether the use of rifampicin E-test strips to screen H. pylori rifabutin resistance is appropriate. Methods A total of 89 H. pylori isolates were included. Rifampicin minimum inhibitory concentrations (MICs) were obtained by E-test, while the MICs for rifapentine, rifaximin, and rifabutin were determined by agar diluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…20 Nevertheless, recent studies have demonstrated that even a breakpoint concentration of 4 mg/L may be a poor marker of rifabutin resistance, so the generalisability of rifampicin resistance to rifabutin may be questionable. 21 The high rate of multidrug resistance seen in the current study (63%) is comparable to what has been reported in various regions of South East Asia. 17 Of these multiresistant strains, 90% had resistance to both clarithromycin and metronidazole, whereas 30% were resistant to levofloxacin.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…20 Nevertheless, recent studies have demonstrated that even a breakpoint concentration of 4 mg/L may be a poor marker of rifabutin resistance, so the generalisability of rifampicin resistance to rifabutin may be questionable. 21 The high rate of multidrug resistance seen in the current study (63%) is comparable to what has been reported in various regions of South East Asia. 17 Of these multiresistant strains, 90% had resistance to both clarithromycin and metronidazole, whereas 30% were resistant to levofloxacin.…”
Section: Discussionsupporting
confidence: 86%
“…However, whereas EUCAST recommends using rifampicin MIC >1.0 mg/L as the rifabutin breakpoint, studies have shown that H. pylori isolates with moderate rifampicin resistance were susceptible to rifabutin, so it has been suggested that rifampicin resistance can be used to screen for rifabutin resistance using a breakpoint of 4 mg/L 20 . Nevertheless, recent studies have demonstrated that even a breakpoint concentration of 4 mg/L may be a poor marker of rifabutin resistance, so the generalisability of rifampicin resistance to rifabutin may be questionable 21 …”
Section: Discussionmentioning
confidence: 99%